MADRASAH HEAD ACADEMIC SUPERVISION IN IMPROVING TEACHER PROFESSIONALISM AT MTSN 2 CIANJUR - Huda, mohamad Yusril; Maulana, Fahri Ali; Khana, Muhammad Amar (Jurnal Administrasi Pendidikan, 2024)
This research aims to explore and analyze the implementation of academic supervision at MTsN 2 Cianjur. A qualitative approach with a single case study method was employed. Data was collected through interviews, observations, and documentation. The findings of the research indicate that MTsN 2 Cianjur has a well-structured system of academic supervision. Academic supervision is conducted regularly by school supervisors and subject coordinators, and peer-to-peer supervision among teachers is also practiced to enhance the quality of teaching and learning. However, the research also revealed some challenges in the implementation of academic supervision at MTsN 2 Cianjur, such as limited time available for supervision and a lack of training for teachers related to supervision. Therefore, it is recommended that MTsN 2 Cianjur improve training for teachers regarding supervision and allocate more time and resources for the implementation of supervision. In conclusion, academic supervision at MTsN 2 Cianjur has been conducted well and in a structured manner, but improvements are still needed in certain aspects. This research is expected to contribute to enhancing the quality of academic supervision at MTsN 2 Cianjur and other schools. Having a well-structured system of academic supervision can help improve the quality of teaching and learning and students' learning outcomes.